Home, sweet home - Pitcher, Caroline; Arthur, Jenny (Languna Hills, CA : QEB Pub., 2008)
Frog, dislodged from his home in an old rusted bucket, is having trouble finding a new place to live, but he gets a bit of unexpected help that lands him in the perfect spot.
2.5
K-3
Keywords: Frogs -- Juvenile fiction; Dwellings -- Juvenile fiction; Frogs -- Fiction; Dwellings -- Fiction; Frogs -- Fiction; Houses -- Fiction